2014
DOI: 10.1080/1357650x.2014.898648
|View full text |Cite
|
Sign up to set email alerts
|

Elevated rates of atypical handedness in paedophilia: Theory and implications

Abstract: Multiple factors determine handedness including genetics, prenatal stress and post-natal environmental conditions. Atypical handedness, whether manifest as increased sinistrality or decreased strength of lateral preference, has been noted in a wide variety of populations with neuropathology. Those with atypical sexual preferences, specifically paedophilia, also manifest reduced rates of right-handedness. This paper uses the largest sample of phallometrically assessed men to date to establish the pattern of aty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 43 publications
(65 reference statements)
1
15
1
1
Order By: Relevance
“…8.8%; c 2 (1, N = 1,712) = 13.62, p < .001]. Interestingly, the laterality quotient also was significantly associated with the subjects' pedophilic phallometric index score (39).…”
Section: Handedness and Androgensmentioning
confidence: 89%
See 1 more Smart Citation
“…8.8%; c 2 (1, N = 1,712) = 13.62, p < .001]. Interestingly, the laterality quotient also was significantly associated with the subjects' pedophilic phallometric index score (39).…”
Section: Handedness and Androgensmentioning
confidence: 89%
“…Babchishin et al, for instance, reported any congenital malformation in 47 out of 654 offenders (7.2%) (35). Fazio et al pointed out that, even though they found a significant relationship between handedness and pedophilia, handedness accounted for only about 0.2% of the variance in pedophilia (39). However, one has to keep in mind that, considering the low base rate of pre-and perinatal anomalies, their explanatory power is rather limited.…”
Section: Prenatal Factorsmentioning
confidence: 99%
“…The phallometric Pedophilia Index was more accurate in distinguishing pedophiles from teleiophiles than the Hebephilia Index was in distinguishing hebephiles from teleiophiles. Such a pattern would be expectable: Empirically, features and correlates of hebephilia frequently fall midway between those of pedophilia and teleiophilia [28], including in terms of IQ [29], handedness [18,[29][30][31], physical height [32], "minor physical anomalies" [33], and histories of school-grade failure or special education placement [34]. Moreover, because prepubescent children are more distinct from adults than are pubescent children, pedophilia would be expected to be more distinct from teleiophilia than is hebephilia, and therefore, easier to distinguish from teleiophilia.…”
Section: Discussionmentioning
confidence: 99%
“…Given the current findings regarding the prevalence of craniofacial anomalies among pedophiles, the relationship between MPAs and non-right-handedness was explored, the latter marker having been previously linked to pedophilia (Cantor et al, 2004(Cantor et al, , 2005bFazio, Lykins, & Cantor, 2014). Consistent with the patternofresultsdescribedthusfar,morecraniofacialanomaliescorresponded to higher rates of non-right-handedness.…”
Section: Discussionmentioning
confidence: 53%